Developing English Listening Comprehension Materials Based on YouTube as a Medium for Second-Grade Students of SMAN 2 Teluk Dalam - Ridwan (PT Inovasi Pratama Internasional, 2024)
One of the initial steps in learning a language is to get accustomed to listening to that language and understanding the meaning and intent of the spoken words. The next step is to follow along, practice, and apply it in everyday life. Listening and reading are considered receptive skills since they involve understanding language without the need to produce it. These skills entail accepting and comprehending language input. The word-guessing method is one of the techniques that can enhance students' speaking and listening skills. This method fosters interactive exchanges, which are highly suitable for improving speaking skills in the learning process. It enables students to enhance their speaking abilities through active participation and engagement.the objective of this research was to knew how effective this method to improved student listening skills. This research was conducted at SMN2Teluk dalam,. The research took place from January to March 2024 during the odd semester of the 2023/2024 academic year. This demonstrated that the development of the listening skill learning material using the youtube by folklore story was highly effective as it significantly improved student achievement. Initially, only 4,76% of students passed this subject, but this increased to 95,23% of students meeting the passing criteria.